PENGARUH PARTISIPASI ANGGARAN TERHADAP KINERJA MANAJERIAL DENGAN GAYA KEPEMIMPINAN DAN KECUKUPAN ANGGARAN SEBAGAI VARIABEL MODERASI (Studi Empiris Seluruh Manajer Rumah Sakit Umum Pemerintah di Provinsi Riau) - Rikotavia Sinuhaji; Nur Azlina; Rusli Rusli (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Ekonomi, 2018)
The purpose of this research was to identify and analyze about (1) The effect of budgetary participation on managerial performance, (2) The effect of budgetary participation on managerial performance with leadership style as moderating variable, and (3) The effect of budgetary participation on managerial performance with budget adequacy as moderating variable. Study was conducted at government general hospital in Riau Province, which amount to 13 general hospital. The data used in this research was primary data with questionnaire as an instrument. The method that used to the sample selection was simple random sampling. The number of samples in this research were 120 respondents. Hypothesis test used in this research was statistical t-test. Data analysis techniques used in this research was multiple linear regression analysis using Statistical Product and Service Solution (SPSS) version 17.0 for Windows as data processing software program. Results of hypothesis test using statistical t-test showed the significant value of budgetary participation variable 0.000 < 0.05, which means that H1 accepted, the leadership style variable 0.006 < 0.05, which means that H2 accepted, and budget adequacy variables 0.000 < 0.05, which means the H3 accepted. The results showed budgetary participation, leadership style, and budget adequacy has effect on managerial performance.Keywords : budgetary participation, managerial performance, leadership style, and budget adequacy.